(untitled) (Mustansiria Dental Journal, 2019)
This study was conducted to evaluate the effect of three different media ( artificial saliva, acidic and alkaline ) and the effect of five times of multiple firing procedure on hardness number of IPS e - max pressable ceramic . Seventy discs shaped specimens were fabricated according to the manufacturer’s instructions. The specimens were randomly divided into seven groups. Three for different media and four for multiple firing procedure ( ten specimens for each group). The groups were subdivided as follows: According to different media: Group 1: specimens will be left in artificial saliva (Neutral media) for 10 days at 37c° in an incubator, Group2: specimens will be left in an acidic media for 10 days at 37c° in an incubator, Group 3: specimens will be left in an alkaline media for 10 days at 37c° in an incubator. According to multiple firing procedures Group 1: specimens will be exposed to firing one time, Group 2: specimens will be exposed to firing 3 times, Group 3: specimens will be exposed 5 times to firing procedures, Group 4: these specimens will be exposed to firing for 7 times. Then each group will be subjected to hardness test using Shore D hardness tester. The statistical analysis of the data of the tested groups of different media revealed that the high hardness values was in the alkaline media, while the lowest hardness values was in the acidic media. The highest hardness values of the firing groups were found in the group of 7 times firing, while the lowest hardness values were found in the group 3 times firing and the results were statistically non significant. As a conclusion, an alkaline media increase the surface hardness of the IPS e – max ceramic, and multiple firing did not affect the surface hardness of the e –max ceramic